1994
DOI: 10.1177/104063879400600218
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Panencephalitis in Puppies Infected with La Crosse Virus

Abstract: Arboviral encephalitis in domestic animals in the United States is rare with the exception of equine encephalomyelitis in horses. 8 This report describes 2 cases in which La Crosse virus (LACV) was isolated from canine littermates with acute clinical encephalitis or sudden death. Both cases occurred in the southern region of the state of Georgia and were submitted as cadavers for necropsy to the Veterinary Diagnostic and Investigational Laboratory (VDIL) in Tifton, Georgia. On May 9, 1988, 4 2-week-old mixed-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…However, several cases of encephalitis of young dogs caused by LaCrosse virus were described in the USA (Black et al 1994;Tatum et al 1999); experimental infection of puppies led to fatal CNS disease (Godsey et al 1988).…”
Section: Mosquito-borne Human Pathogenic Viruses Autochthonous In Europementioning
confidence: 99%
“…However, several cases of encephalitis of young dogs caused by LaCrosse virus were described in the USA (Black et al 1994;Tatum et al 1999); experimental infection of puppies led to fatal CNS disease (Godsey et al 1988).…”
Section: Mosquito-borne Human Pathogenic Viruses Autochthonous In Europementioning
confidence: 99%
“…10,36,39,44 LaCrosse virus (LACV) encephalitis, a rare disease in both human and veterinary medicine, is also an important arboviral disease in the United States. 6,10,44 Here, we describe an LACV central nervous system infection in a dog, which may also be affecting the children associated with this animal.…”
mentioning
confidence: 99%
“…8 In a previous study, osteophytes were found in the lumbar vertebrae of adult boars, but they did not cause vertebral canal stenosis. 3 Vertebral fractures have been associated with lactation osteoporosis, 6 electrocution, 1 and suppurative spondylitis. 2 Lumbar vertebral abscesses with or without vertebral fracture is the most frequent cause of paresis/paralysis diagnosed in pigs submitted to this laboratory.…”
mentioning
confidence: 99%
“…Two serologic studies from the United States ( 7 ) and Mexico ( 8 ) found antibodies against La Crosse virus, South River virus, and Jamestown Canyon virus in dogs. Two other reports described cases in which La Crosse virus was detected in canine littermates who had clinical encephalitis ( 9 ) or neurologic disorders ( 10 ).…”
mentioning
confidence: 99%